IMAGERY IN SONG LYRICS OF ALICIA KEYS - Unpris Yastanti; Dewi Safitri (Center of Language and Cultural Studies [CLCS], 2016)
The objective of this study is to identify kinds of imagery on songs lyric of Alicia Keys. This study used descriptive method to analyze data. Recorder songs lyrics of Alicia Keys were served as resources of data and imagery reflected in the lyrics was promoted as data of this study. The study revealed the following findings: (1) imagery was deserved in three lyrics of Alicia Keys: Girl on Fire, Superwoman, and A Woman’s Worth, (2) Kinds of imagery in the three lyrics songs included: auditory imagery, kinesthetic imagery, visual imagery and organic imagery and the forming is about a woman life, (3) Message of songs figured out upon a woman’s life, suggesting a woman should undertake real struggle and never gave up at whatever occurred in life.